Don?t ignore the traditional communicators - Jallow, Issatou (Technical Centre for Agricultural and Rural Cooperation, 2005)
Director of the National Nutrition Agency in The Gambia describes the new priority being given to nutrition in her country, and the value of traditional communicators in spreading health messages.